Certificate Application at the Web-Based Human Resources Development Agency (BPSDM) of North Sumatra Province - Yulia, Anisa; Triase (Journal of Computer Science and Informatics Engineering, 2023)
Badan Pengembangan Sumber Daya Manusia North Sumatra Province is a government agency that supports the goal of the Governor of North Sumatra to build trustworthy and competitive human resources. In BPSDM North Sumatra Province, especially in the field of Managerial Competency Development has a task, one of which is to make certificates which are currently still conventional using Microsoft Word and Microsoft Excel so that a solution is needed to build a certificate application where PHP and MySQL programming languages are used using the stages of designing a user centered design (UCD) system. So that this application can be used for making certificates in the field of Managerial Competency Development to complete certificates in a fast time. Based on the test results using blackbox, each menu in the certificate application has been successfully used properly.